Student Teachers’ Views on Grammar and Grammar Teaching, and its Communication to their Students (Journal of NELTA, 2018)
The present article builds on the study entitled “English Grammar: Views of Student Teachers and Communication of Grammar to their Students” carried out under and submitted to University Grants Commission, Nepal. The study adopted the mixed-methods of questionnaire and semi-structured classroom observation. Against a brief theoretical background of grammar and grammar teaching and review of the related literature, the article presents respondent teachers’ views on grammar and grammar teaching collected by means of a set of questionnaire. Their views are further compared with the classroom data collected by observation. It is found that there is a lack of congruence between the teachers’ views, and their actual classroom practices in the areas, such as methods, techniques, resources and activities. Finally, the article presents conclusion and some pedagogical recommendations for teachers and teacher educators. Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, page: 89-102